THE EXPECTATION AND SATISFACTION LEVELS OF EDUCATIONAL FACULTY STUDENTS ABOUT MANAGERIAL AND ACADEMIC SERVICES - Eris, Hasan; Capkiner, Hatice (Hacettepe Univ, 2012)
Majority of the university students have big expectations when they begin university life and their ideas for achieving these expectations reveal the degree of their university expectations. Individual, institutional and social competition makes it obvious to reach the peak in information society especially an intensive competition among universities. It will be advantageous to give importance and priority for universities and conduct this type of researches to present more qualified services for competitors in such a competitive environment. This study aims to present the degree of expectations and satisfaction of the students of Education Faculty by taking into consideration physical conditions of the faculty, courses, management characteristics and instructors. Small difference between expectation and satisfaction of the university shows that students' expectations are met with good performance, when there is a big difference it shows that performance is not good in a particular area. On the other hand, when the degree of expectations is high and satisfaction degree is low universities should use intervention immediately and create development programs. When the degree of expectation and satisfaction are high, universities are considered to be strong in providing academic services and advantages. When the degree of expectation is low and the degree of satisfaction is high, universities exceed the services of expectations of the students, but this situation is very rare.
Keywords: Expectation; satisfation level; manargial and academic services